Fermentation Characteristics and Sensory Evaluation of Durian Yoghurt as a Synbiotic with Skim Milk and Sugar Formulations: English - Romadhon, Taufikkilah; Emmawati, Aswita; Marwati, Marwati; Yuliani, Yuliani; Rahmawati, Rini; Martati, Martati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Synbiotic products are a combination of probiotics and prebiotics in food that work synergistically to enhance the survival of beneficial microbes and provide greater health benefits. Durian contains simple sugars, dietary fiber, and oligosaccharides that can be utilized by probiotics as a nutrient source for their growth. This study aims to evaluate the potential of durian (Durio zibethinus) as a prebiotic ingredient in the formulation of synbiotic yoghurt by observing its effects on fermentation characteristics, including microbiological, chemical, and sensory properties, when combined with different concentrations of skim milk and sugar (0%, 5%, and 10%). Total bacteria, lactic acid bacteria (LAB), and titratable acidity increased, while the pH value of the product decreased during the fermentation process. The addition of skim milk and sugar influenced the sensory profile of the product, with the best treatment observed in skim milk and sugar 5% (P8), ba Synbiotic products are a combination of probiotics and prebiotics in food that work synergistically to enhance the survival of beneficial microbes and provide greater health benefits. Durian contains simple sugars, dietary fiber, and oligosaccharides that probiotics can utilize as a nutrient source for their growth. This study aims to evaluate the potential of durian (Durio zibethinus) as a prebiotic ingredient in the formulation of synbiotic yoghurt by observing its effects on fermentation characteristics, including microbiological, chemical, and sensory properties, when combined with different concentrations of skim milk and sugar (0%, 5%, and 10%). Total bacteria, lactic acid bacteria (LAB), and titratable acidity increased, while the pH value of the product decreased during the fermentation process. The addition of skim milk and sugar influenced the sensory profile of the product, with the best treatment observed in skim milk and sugar 5% (P8), based on hedonic scores for aroma, texture, and taste of the yoghurt after 24 hours of fermentation. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Actionased on hedonic scores for aroma, texture, and taste of the yoghurt after 24 hours of fermentation.